CHANGES IN BLOOD PARAMETERS OF GRASS CARP CTENOPHARYNGODON IDELLA (VALENCIENNES, 1844) FINGERLINGS UNDER THE EFFECT OF CHLOROFETE - AL-SAADI, A. G. Y.; ALI, T. S. (Iraqi Journal of Aquaculture, 2022)
The present study has carried out to clarify the changes of blood parameters of grass carp Ctenopharyngodon idella (Valenciennes, 1844), responding to chlorofete effect under laboratory conditions, in the presence and absence of aquatic plant Ceratophyllum demersum (L.). Three concentrations used during chronic exposure time extended to (15days). Blood tests of (R. B. Cs., Hb, P.C.V.) were studied for fish exposed to concentration investigated. The hematological parameters decreased with the increasing of pesticide concentrations. Moreover, values of indices (M.C.V.) showed significant increase with the increasing of pesticide concentration, particularly at highest concentration used (3.8) mg/l during (5, 6 and 9) days with absence aquatic plant. However, apparent increasing of (M.C.H.) were observed at especially at concentration of (3.8) mg/l during (6 and 9) days of exposure time. Significant increasing were recoded in (M.C.V.) values for treatment aquatic plant during (7 and 10) days at concentration (3.8) mgł and during (10) days for (M.C.H.). The present study showed nonsignificant reduction in (M.C.H.C.) values for both treatments with and without aquatic plant.